The Impact of Digital Technology Literacy and LifeSkills On Poverty Reduction - Parianom, Raden; Arrafi J, Indri; Desmintari, Desmintari (Green Publisher Indonesia, 2022)
Various national and regional level reports project that Indonesia's economic growth will be driven by the development of digital technology. Das et al. (2016) predicts that, by 2025, digitalization will have an impact of 150 billion US dollars (US) and additional jobs for 3.7 million people. This potential can be seen from, among other things, the number of start-up technology companies (or commonly referred to as startups) which is growing significantly.). Das et al. (2018) also projects that the potential for electronic commerce (e-commerce) in Indonesia in 2022 will reach 55 billion to 65 billion dollars. The impact will be felt on the absorption of labor, including female workers. This calculation gives great hope for Indonesia to accelerate its economic growth. However, to what extent can growth driven by the development of the digital economy guarantee an increase in the quality of life for all levels of society? Can the digital economy in the future reduce inequality which is currently quite high? Furthermore, the Life Skills program is intended to improve the Life Skills ability which is specifically organized to provide learning opportunities for young people of productive age in order to acquire knowledge, skills and develop an entrepreneurial spirit which is supported by a creative, innovative, professional, responsible mental attitude, and dares to take risks. in managing their potential and their environment as a provision to improve their quality of life. The purpose of this study is to analyze the role of digital literacy in economic technology and the role of life skills programs in reducing poverty.